Dampak Siklon Tropis Seroja Terhadap Ketersediaan Pakan, Tempat Bersarang dan Pendapatan Petani Lebah Madu Hutan (Apis dorsata) - Ofliyani Yeni Sanrina Tabana; Maria M. E. Purnama; Nixon Rammang (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
This study aims to determine the impact of the availability of forest honey bee feed, the impact of forest honey bee nesting sites and the impact of changes in the income of forest honey bee farmers in Uiasa Village, Semau District, Kupang Regency, East Nusa Tenggara before and after the Tropical Cyclone Storm Seroja. This research was carried out around the Pastello Amalato Protected Forest Area, Uiasa Village, Semau District, Kupang Regency, which was carried out for 1 month, from April to May 2022. This research used purposive sampling, interview and roaming methods with data analysis using descriptive qualitative and descriptive analysis. quantitative.The impact of food availability after the Seroja Tropical Cyclone Storm consists of two factors, namely reduced forage for forest honey bees and disruption of the flowering time of forage plants. The impact of forest honey bee nesting after the Seroja tropical cyclone storm was influenced by the movement of forest honey bee hives from their original place to another and the altitude where the forest honey bee nest trees were found was mostly at an altitude of 25-45 meters above sea level compared to other elevations with the number of honey bee trees is 10 trees and 7 trees at an altitude of 0-25 meters above sea level.